Relationship between stress response and mitochondrial respiration in skeletal muscle of apolipoprotein E4 (APOE4) carriers. (20th December 2022) - Johnson, Chelsea N.; Thyfault, John P; McCoin, Colin S.; Swerdlow, Russell H; Wang, Xiaowan; John, Casey S.; Geiger, Paige C; Morris, Jill K.
Abstract: Background: Expression of the stress‐inducible chaperone protein, heat shock protein 70 (HSP70/72), is elevated in the Alzheimer's disease (AD) brain. This may result from mitochondrial stress, as AD mitochondria are characterized by reduced complex IV activity and ATP levels. Further, patients with mild cognitive impairment (MCI) have reduced lipid‐stimulated mitochondrial respiration in skeletal muscle, providing evidence that mitochondrial dysfunction occurs peripherally, manifests early in the disease, and is related to lipid metabolism. Interestingly, the primary genetic risk factor for sporadic AD, the apolipoprotein E4 (APOE4) allele, plays an important role in lipid metabolism. The goal of this study was to characterize the skeletal muscle stress response in APOE4 carriers and the relationship with muscle mitochondrial function. Method: We analyzed skeletal muscle tissue from previously collected biopsies (vastus lateralis) from 23 older adults (65+) who were cognitively healthy (CH, n=8) or MCI (n=15) and at genetic risk for AD (APOE4 carriers). We measured HSP72 protein levels via Western blot and leveraged previously collected data on APOE4 genotype, mitochondrial respiration (basal, state 3, state 3S, uncoupled), plasma cholesterol and platelet citrate synthase activity, the latter of which is a marker of mitochondrial content. Analyses were controlled for age and sex. Result: HSP72 expression negatively correlated with basal respiration (R 2 = 0.518, p = 0.002), ADP‐stimulated respiration (R 2 = 0.775, p = <0.001) and succinate‐stimulated respiration (R 2 = 0.405, p = 0.011) in the presence of the lipid, palmitoyl‐carnitine, in skeletal muscle of APOE4 carriers with MCI, but not in CH APOE4 carriers. HSP72 expression negatively correlated with platelet citrate synthase activity (R 2 = 0.518, p = 0.002) in APOE4 carriers with MCI, but not in CH APOE4 carriers. HSP72 expression positively correlated with plasma cholesterol in all participants (R 2 = 0.182, p = 0.042). Conclusion: This work supports a potential role for the heat shock response in responding to peripheral mitochondrial dysfunction and elevated cholesterol levels during cognitive decline in APOE4 carriers. Further work is needed to determine if this stress response serves a protective role.